Management Practices in the Ancient Vedas (Global Journal of Management and Business Research, 2017)
This paper presents an analysis of the concepts associated with the study and practice of Management in view of the changing world order while establishing their inter relatedness with the theories and practices developed in the West. Being followed by the leaders and entrepreneurs of the country right from the Vedic ages, the ancient Indians had developed their own management systems with the help of which they successfully carried out their business affairs. It is our hypothesis that the practices, thus cultured and the concepts thus evolved, are relevant across the boundaries of time and space, and shall be immensely helpful for the organizations of the west as well. The Vedas and Upanishads have been at the grass root of Indian Literature work on culture and wisdom of ancient time. This study focuses on enriching the modern management terminology by the implication of the Vedic management system.
Keywords: vedas; vedangas; upanishads; excellence; karma; bhagwadgita; management